Effects of Interleukin-18 on Cardiac Fibroblast Function and Gene Expression - Fix, Charity (2010)
Fibroblasts are the primary cell type responsible for synthesis and remodeling of the extracellular matrix in the heart. A number of factors including growth factors, hormones and mechanical forces have been identified that modulate the production of extracellular matrix by cardiac fibroblasts. Inflammatory mediators including proinflammatory cytokines and chemokines also impact fibrosis of the heart. Recent studies have illustrated that interleukin-18 promotes a pro-fibrotic response in cardiac fibroblasts; however the effects of this cytokine on other aspects of fibroblast function have not been examined. While fibroblasts have long been known for their role in production and remodeling of the extracellular matrix, other functions of these cells are only now beginning to be appreciated. We hypothesize that exposure to interleukin-18 will stimulate other aspects of fibroblast behavior important in myocardial remodeling including proliferation, migration and collagen reorganization. Fibroblasts were isolated from adult male rat hearts and bioassays performed to determine the effects of interleukin-18 on fibroblast function. Treatment of fibroblasts with interleukin-18 (1–100 ng/ml) resulted in increased production of extracellular matrix components and remodeling or contraction of three-dimensional collagen scaffolds by these cells. Furthermore, exposure to interleukin-18 stimulated fibroblast migration and proliferation. Treatment of heart fibroblasts with interleukin-18 resulted in the rapid activation of the c-Jun N-terminal kinase (JNK) and Phosphoinositide 3-kinase (PI3-kinase) pathways. Studies with pharmacological inhibitors illustrated that activation of these pathways is critical to interleukin-18 mediated alterations in fibroblast function. These studies illustrate that interleukin-18 plays a role in modulation of cardiac fibroblast function and may be an important component of the inflammation- fibrosis cascade during pathological myocardial remodeling.